Interventions to reduce work-related musculoskeletal disorders among healthcare staff in nursing homes; An integrative literature review - Enobong Gideon Asuquo; Sylvia Murphy Tighe; Carmel Bradshaw (Elsevier, 2021)
Background: : The incidence of work-related musculoskeletal disorders have been consistently high in nursing sectors and are a significant cost to the health service due to absenteeism. Work-related musculoskeletal disorders are more common among healthcare workers in nursing homes due to the high dependency needs of older persons which often include need for help with self-care and mobility. Therefore, staff are exposed to potential injury associated with moving and handling patients. Work-related musculoskeletal disorders significantly impact on the quality of life of affected individuals, can cause economic hardship and affect service provision. Aim: : To identify, review, and discuss interventions that may be effective in reducing the prevalence and consequences of work-related musculoskeletal disorders in nursing homes. Design: : An integrative literature review. Method: : A systematic search of Embase, Science direct, Web of science and EBSCO Host was conducted and an ancestry search of the references of the reviewed articles were also reviewed. Peer reviewed primary research published between 2000 and 2020 were selected. The quality of these studies was appraised with Crowe Quality Appraisal Tool and reported using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The components of the interventions were categorised using Burnard (2011) framework for content analysis. Results: : Fifteen studies met the criteria for inclusion in the review. Interventions reported in the literature were in four categories; (i) Specialised equipment (ii) Staff training (iii) Policies and procedures to reduce work-related musculoskeletal disorders and (iv) Support and follow up. A ceiling lift is the intervention of choice to reduce work-related musculoskeletal disorders, as it reduces the stress associated with pushing and pulling. Risk assessment is vital to determine the individual needs of clients for safe handling. Train-the-trainer roles could be used to implement training interventions where resources limit the employment of a designated lead to facilitate injury prevention. A multifaceted approach to prevent and reduce work-related musculoskeletal disorders is recommended. Further research is required to ascertain the effectiveness of Cognitive Behavioural Therapy on injury reduction in nursing homes. Conclusion: : These findings have the potential to inform the development and adherence to injury prevention policies and regulations by healthcare managers and staff which could reduce injuries. Identifying the appropriate interventions to prevent and reduce work-related musculoskeletal disorders is significant for staff wellbeing, has economic implications in terms of reduced work-related musculoskeletal disorder absenteeism and ultimately will positively impact on the care of mobility impaired clients.